Mineralogical Controls on Scandium Enrichment in Nickel Laterites of Wolo, Southeast Sulawesi, Indonesia (Iraqi National Journal of Earth Science (INJES), 2026)
Nickel laterite deposits, enriched in critical metals such as nickel (Ni) and scandium (Sc), have gained significant attention due to their economic and technological importance. This study investigates the mineralogical and geochemical factors that influence scandium enrichment within the nickel laterites of Wolo, Southeast Sulawesi, Indonesia. The research focuses on the distribution and accumulation of scandium within the laterite profile, with particular emphasis on the limonite zone, and explores the geochemical processes that contribute to this enrichment. Geochemical analysis of 12 samples from three drill holes reveals a progressive increase in scandium concentrations, from 9–14 ppm in unweathered harzburgite to a peak of 82 ppm within the limonite horizon. This enrichment is accompanied by a substantial rise in iron (Fe) content, which increases from 5.71–6.34 wt.% in the bedrock to 43.19 wt.% in the laterite zones. X-ray diffraction (XRD) analysis identifies goethite and gibbsite as the key minerals involved in scandium accumulation. Furthermore, a positive correlation is observed between scandium and iron oxides, particularly goethite, while a negative correlation is noted with magnesium oxide (MgO). This study provides an understanding of the geochemical mechanisms driving scandium enrichment and highlights the role of iron oxides in this process
Keywords: Mineralogy, Nickel laterite, Geochemical, Scandium enrichment, Indonesia.